Analytical study of Emotional Balance for Some Fundamental Skills in Iraqi Futsal Clubs - Abdulmajeed, Teeba Saleem; yasser, Nada (Journal of Physical Education, 2021)
The research aimed at constructing an emotional balance scale for Iraqi futsal clubs as well as identifying the level of emotional balance scale for Iraqi female futsal players. It also aimed at identifying the psychological and obstacles that female futsal players face in training and during competition. The researchers used the descriptive method on (300) female futsal players who represent (20) clubs distributed as a pilot study, main experiment, construction, and applications subjects. The scale consisted of (26) items to come up with the rests. The data was collected and treated using SPSS to conclude that the results showed significance between emotional balance and mental, social, motor, psychological stability, and courage in facing the future.